Speaking of dying : recovering the church's voice in the face of death - Craddock, Fred B., Jr., 1928-2015.; Goldsmith, Dale.; Goldsmith, Joy V. (Grand Rapids, MI : Brazos Press, 2012)
"The church does not cope very well with dying. Instead of using its own resources to mount a positive end-of-life ministry for the terminally ill, it outsources care to secular models, providers, and services. A terminal diagnosis typically triggers denial of impending death and placing faith in the techniques and resources of modern medicine. If a cure is not forthcoming, the patient and his or her loved ones experience a sense of failure and bitter disappointment. This book offers a critical analysis of the church's failure to communicate constructively about dying, reminding the church of its considerable liturgical, scriptural, and pastoral resources when it ministers to the terminally ill. The authors, who have all been personally and professionally involved in end-of-life issues, suggest practical, theological bases for speaking about dying, communicating with those facing death, and preaching about dying. They explore how dying--in baptism--begins and informs the Christian's life story. They also emphasize that the narrative of faith embraces dying, and they remind readers of scriptural and christological resources that can lead toward a 'good dying.' In addition, they present current best practices from health professionals for communication among caregivers and those facing death"--Publisher description.
The dying pastor: everybody knew, but no one would talk about it -- Victims of the wrong story -- Jesus Christ: Lord of the living and the dead, and the dying -- The difference Jesus's dying makes -- What do you say to someone who is dying? -- Preaching on death and dying -- Facing dying faithfully: a small cloud of witnesses -- A good dying.
Includes bibliographical references and index.
Keywords: Death -- Religious aspects -- Christianity